A Two‐in‐One Annealing Enables Dopant Free Block Copolymer Based Organic Solar Cells with over 16% Efficiency. Issue 6 (2nd February 2023) - Yao, Shangfei; Yang, Linji; Shi, Shasha; Zhou, Yang; Long, Min; Zhang, Wenhao; Cai, Songlin; Huang, Ciyuan; Liu, Tao; Zou, Bingsuo
Comprehensive Summary: The organic solar cells (OSCs) based on block copolymer systems bear the hope of achieving the optimal balance of power conversion efficiency (PCE) and stability, but the key index, PCE of this type devices is still low. To improve the efficiency, regulating the thin‐film morphology is always the core engineering, which is usually achieved via two aspects: precursor optimization and post treatments. Herein, we extend our previous success in post treatments (two step annealing) to a novel two‐in‐one annealing tactic, which realizes limited phase separation and well‐connected domain distribution. As a result, the optimal PCE as high as 16.08%, representing the cutting‐edge level of block copolymer based OSCs (notably dopant free). Furthermore, a comprehensive study on all kinds of annealing methods is carried out, including TA, SVA, SVA+TA, TA+SVA and SVTA (the best one), and an in‐depth understanding is demonstrated, with the help of different characterizations. Abstract :